Mask-wearing behavior patterns among dental patients in post-pandemic China: a cross-sectional study - Zhu, Junfei; Lin, Fang; Yuan, Xuguang (Frontiers in Public Health, 2025)
BackgroundThe present study investigated the demographic characteristics of individuals who wear masks when visiting the Dental Department of a public Hospital in Beijing, China, 2 years after the Chinese government relaxed mask mandates following the COVID-19 pandemic.MethodsA cross-sectional study was conducted at the Dental Department of China–Japan Friendship Hospital. Patients visiting the Clinic of the Stomatology Center were observed. Data on mask-wearing status, age, gender, outdoor temperature, and weather conditions were recorded. Statistical analyses included chi-squared tests and binary logistic regression to identify predictors of mask use.ResultsAmong 1,009 patients, 46.3% wore masks. Females exhibited significantly higher mask-wearing rates than males (62.0% vs. 19.6%, OR = 6.457, P < 0.001). The increase of age positively influenced the mask-wearing rates (OR 1.010, P = 0.046). Lower temperatures (0–19°C) correlated with higher mask wearing rates (56.2–57.0%) versus warmer groups (20–39°C, 38.6–42.0%, P < 0.001), with each degree increase reducing likelihood by 2.3% (OR = 0.977; P = 0.007). Significantly elevated mask-wearing rates were observed during foggy weather conditions.ConclusionNearly half of patients continue to wear masks when visiting the Dental Department in the post-pandemic era. The mask wearing behavior was influenced by gender, age, and environmental factors such as outdoor temperature and weather. Females and older individuals showed higher adherence, while colder temperatures and foggy weather correlated with increased mask use.